Animalopters-towards a new dimension of flight mechanics - Goszczyński, Jacek A.; Lasek, Maciej; Pietrucha, Józef; Sibilski, Krzysztof (Transport, 2002)
Recently, it has been recognised that flapping wing propulsion can be more efficient than conventional propellers if applied to very small-scale vehicles, so-called MAVs (micro air vehicles). Extraordinary possibilities of such objects, particularly in the context of special missions, are discussed. Flapping flight is more complicated than flight with fixed or rotating wings. Therefore, there is a need to understand the mechanisms of force generation by flapping wings in a more comprehensive way. The paper describes the current work on flapping wing conducted by the Flying & Swimming Puzzle Group. The key to understand the mechanisms of flapping flight is the adequate physical and mathematical modelling; modelling problems of flow and motion are emphasised. Sample calculations illustrating current capabilities of the method have been performed. The effect of feathering amplitude, flapping amplitude, and phase shifting on the MAV&s control effectiveness has been examined. It has been discovered that the parameters mentioned above can be considered as control parameters of “flapping wing” MAVs, especially in lateral direction. Research programmes for the construction of MAYs concentrate on understanding the mechanisms of animal flight and on creating smart structures which would enable flight in micro-scale. First Published Online: 19 Dec 2011